Bridging production factors allocation and sustainable operations in China's heavy-polluting firms: The moderation effect of internationalization. (15th May 2021) - Liu, Tiansen; Bi, Jun; Xing, Xinpeng; Zhu, Yue; Wang, Jiayu; Yu, Shuao
Abstract: Following 1427 firm-year observations of China's heavy-polluting firms because of their significant impacts on climate change, substantial contributions to industrial prosperity, and distinctive governance structure, this study elaborates if firms' internationalization improves the impact of production factors allocation on sustainable operations. We investigate 5 types of production factors, i.e. capital (asset-liability ratio), labor (production-typed staff size), technology (R&D intensity), information (inventory size), and institution (state-holding size). Empirical findings show that fewer production-typed staff, higher R&D intensity, and higher state-holding all significantly improve sustainable operations, while internationalization is adverse to sustainable operations significantly. Meanwhile, internationalization exercises a significant moderation relationship between production factors allocation and sustainable operations, which is embodied in that the emergence of internationalization encourages slack production factors and varied factors structures to contribute to sustainable operations. Moreover, heterogeneity test sees that there is no obvious difference in the moderation effect of higher and lower degrees of internationalization except such effect exerted on R&D intensity. This study inspires emerging economies' heavy-polluting firms to enrich the influence path of production factors on sustainable operations by involving in global markets. We therefore suggest using slack resources or varied resources structures matching the high degree of internationalization to promote business sustainability. Highlights: We focus on how internationalization moderates the influence of production factor allocation on sustainable operations. Less production-typed staff, higher R&D intensity, and higher state-holding significantly improve sustainable operations. Internationalization significantly negatively affects sustainable operations. There is no obvious difference in the moderation effect of higher and lower internationalization degrees. We suggest using slack production factors and higher internationalization to promote sustainable operations.